Consider the following functions.Step 3 of 4: Find (f g)(-1). Simplify your answer.Answerf(x) = x² + 6 and g(x) = -x +5(-2)-1)=
![Consider the following functionsStep 3 of 4 Find f g1 Simplify your answerAnswerfx x 6 and gx x 521 class=](https://us-static.z-dn.net/files/db3/21db2f0c0347d33b2845b63c6c41bc99.png)
Solving for (f•g)(-1)
[tex]\begin{gathered} (f\cdot g)(x)=f(x)\cdot g(x) \\ (f\cdot g)(x)=(x^2+6)\cdot(-x+5) \\ (f\operatorname{\cdot}g)(-1)=((-1)^2+6)\operatorname{\cdot}(-(-1)+5) \\ (f\operatorname{\cdot}g)(-1)=(1+6)\cdot(1+5) \\ (f\operatorname{\cdot}g)(-1)=7\cdot6 \\ \\ \text{Therefore, }(f\operatorname{\cdot}g)(-1)=42 \end{gathered}[/tex]